2002
DOI: 10.2223/jped.661
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and evolution of bacterial meningitis in a pediatric center

Abstract: Artigo submetido em 30.10.00, aceito em 08.08.01. ResumoObjetivo: determinar a prevalência dos agentes etiológicos das meningites bacterianas em serviço de referência, no atendimento de doenças infecciosas para o estado de Minas Gerais, e verificar a resposta ao tratamento utilizado.Métodos: estudo descritivo em que foram incluídas todas as crianças com diagnóstico provável de meningite, admitidas na instituição no período de junho a novembro/99.Resultados: obteve-se 210 casos de meningite, sendo 111 casos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
1
1
1
Order By: Relevance
“…The existence of 76.92% of aetiological indetermination observed in 50 of 65 cases in the present study, much higher than previous reports, 8 points out the need for the improvement of laboratory procedures, storage and transport conditions of CSF samples. The inability of establishing a deÞ nitive aetiological diagnosis may be due to several factors such as the inoculum size or the previous use of antimicrobial drugs.…”
Section: Discussioncontrasting
confidence: 69%
“…The existence of 76.92% of aetiological indetermination observed in 50 of 65 cases in the present study, much higher than previous reports, 8 points out the need for the improvement of laboratory procedures, storage and transport conditions of CSF samples. The inability of establishing a deÞ nitive aetiological diagnosis may be due to several factors such as the inoculum size or the previous use of antimicrobial drugs.…”
Section: Discussioncontrasting
confidence: 69%
“…This last study, considering the etiology and the mean length of hospitalization of patients without complications (therefore excluding patients with complications and death) encountered 13.2 days, 8.4 days and 10.6 days for H. influenzae, N. meningitidis and S. pneumoniae, respectively. [20] Another study found that, unlike other age groups, in which most had length of stay less than or equal to 10 days (ranging from 87% in 10-14 years and 57% in those over 50), most patients with DM under one year old were hospitalized for more than 15 days -41% in this age range, compared to 9% of the total, have a longer hospital stay. [6] The average age in our sample was around 13 years, which in several series (with no age limits) was between 4-6.…”
Section: Discussionmentioning
confidence: 94%
“…Es importante destacar las dificultades encontradas. En 36% de los casos, la definición entre etiología bacteriana o viral no fue posible, ya sea porque los pacientes estaban usando antibióticos en el momento de la recolección de las muestras para cultivo, ya sea porque las características del LCR no permitieron esa diferenciación, o aun por dificultades técnicas relacionadas a los métodos de laboratorio utilizados.Ese elevado índice de fallas de identificación de los agentes etiológicos en el estudio de meningitis ya ha sido reportado por otros autores17 .…”
unclassified